aP2-Cre-mediated inactivation of estrogen receptor alpha causes hydrometra. - Per Antonson (Public Library of Science (PLoS), 2014)
In this study we describe the reproductive phenotypes of a novel mouse model in which Cre-mediated deletion of ERα is regulated by the aP2 (fatty acid binding protein 4) promoter. ERα-floxed mice were crossed with transgenic mice expressing Cre-recombinase under the control of the aP2 promoter to generate aP2-Cre/ERα(flox/flox) mice. As expected, ERα mRNA levels were reduced in adipose tissue, but in addition we also detected an 80% reduction of ERα levels in the hypothalamus of aP2-Cre/ERα(flox/flox) mice. Phenotypic analysis revealed that aP2-Cre/ERα(flox/flox) female mice were infertile. In line with this, aP2-Cre/ERα(flox/flox) female mice did not cycle and presented 3.8-fold elevated estrogen levels. That elevated estrogen levels were associated with increased estrogen signaling was evidenced by increased mRNA levels of the estrogen-regulated genes lactoferrin and aquaporin 5 in the uterus. Furthermore, aP2-Cre/ERα(flox/flox) female mice showed an accumulation of intra-uterine fluid, hydrometra, without overt indications for causative anatomical anomalies. However, the vagina and cervix displayed advanced keratosis with abnormal quantities of accumulating squamous epithelial cells suggesting functional obstruction by keratin plugs. Importantly, treatment of aP2-Cre/ERα(flox/flox) mice with the aromatase inhibitor Letrozole caused regression of the hydrometra phenotype linking increased estrogen levels to the observed phenotype. We propose that in aP2-Cre/ERα(flox/flox) mice, increased serum estrogen levels cause over-stimulation in the uterus and genital tracts resulting in hydrometra and vaginal obstruction.